Philanthropic Behavior Among Generation Z: A Literature Review On The Drivers Of Social Generosity In The Digital Age - Mohammad Ridwan; Fitri Faujiah; Ambar Larasati; Berri Prima (Journal of Management Economic and Financial, 2026)
The rapid advancement of digital technology has transformed philanthropic activities from conventional methods to digital platforms that offer greater accessibility, convenience, and transparency. This shift has significantly influenced Generation Z, a digitally native generation that actively engages with social media and online platforms. This study aims to examine the factors influencing Generation Z's philanthropic behavior in the digital era. A descriptive qualitative approach was employed using a literature review method. Data were collected from scientific articles published between 2021 and 2026 and indexed in Google Scholar, SINTA, and the Directory of Open Access Journals (DOAJ). The data were analyzed through content analysis to identify and synthesize the main factors shaping philanthropic behavior among Generation Z. The findings reveal that philanthropic behavior is influenced by both internal and external factors. Internal factors include empathy, humanitarian values, and the desire for self-expression and identity formation, while external factors involve the convenience of digital technology, transparency in fund management, peer influence, and the impact of social media and influencers. Generation Z also tends to practice micro-donating by making small but frequent contributions through digital platforms. The study concludes that digital philanthropy has evolved beyond social responsibility, becoming an integral part of Generation Z's digital lifestyle and social engagement.